THE DETERMINANTS OF INDONESIAN STUDENTS’ MATHEMATICS PERFORMANCE: AN ANALYSIS THROUGH PISA DATA 2015 WAVE - M. Mujiya Ulkhaq (LPSDI Bina Patria, 2023)
This study investigates the determinants of Indonesian students’ performance of mathematics proxied by plausible value (PV) of mathematics provided by OECD PISA. The PISA 2015 data is used to answer this research question. A multivariate linear regression is used; as the dependent variable is PV of mathematics, while the information concerning student’s background is used as independent variables, i.e., student’s personal characteristics: age and gender; family background: index of economic, social, and cultural status as well as ICT possession at home; and classroom’s climate: perceived feedback from teacher. Result shows that all determinants but student’s gender are significant at the level of 5%. Several tests to examine the classical assumptions, such as normality of the residuals, test for heteroscedasticity and collinearity are performed. According to these tests, no severe problems occur.